Association of Pesticide Exposure with Anemia in Women Farmers in Bandungan Village, Semarang District - Kartini, Sri; Setiani, Onny; Joko, Tri (International Journal of English Literature and Social Sciences (IJELS), 2019)
One of the causes of anemia is the use of inappropriate pesticides. The body exposed to pesticides causes blood profile abnormalities because pesticides interfere with the organ of blood cell formation, and the immune system. Studies from all over the world have shown negative effects on health from pesticides commonly used in agricultural activities.The study aimed to analyze the correlation of pesticide exposure with the incidence of anemia in women farmers in the agricultural area of Bandungan Su-District, Semarang District. This research was observational type with cross sectional design. The sampling technique was nonprobability sampling with purposive sampling. The number of samples in this study were 50 women farmers. The results of this study that there were association between duration of pesticide spraying, the number and type of pesticides used with anemia in women farmers in Bandungan Village, Semarang District. There were no association between cholinesterase level with anemia in women farmers in Bandungan Village, Semarang District. The conclusion of the research that there was association between pesticide exposure with anemia in women farmers in Bandungan Village, Semarang District.